2006
DOI: 10.1177/0961203306069972
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and non-traditional risk factors contribute to the development of accelerated atherosclerosis in patients with systemic lupus erythematosus

Abstract: To determine risk factors of accelerated atherosclerosis in patients with systemic lupus erythematosus (SLE), 72 patients with inactive disease and 36 age- and sex-matched controls were included. The intima-media thickness (IMT) of the common carotid artery was determined by ultrasound. Traditional risk factors and disease-related factors were recorded. Cardiovascular risk was estimated using SCORE (systematic coronary risk evaluation). Markers of inflammation, endothelial activation and vascular remodelling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 30 publications
6
66
1
2
Order By: Relevance
“…This was in accordance with the study of de Leeuw et al, who found CRP significantly higher even in inactive SLE patients [23]. Another study found hs-CRP to be significantly higher in SLE [24] .…”
Section: Discussionsupporting
confidence: 92%
“…This was in accordance with the study of de Leeuw et al, who found CRP significantly higher even in inactive SLE patients [23]. Another study found hs-CRP to be significantly higher in SLE [24] .…”
Section: Discussionsupporting
confidence: 92%
“…Older age at diagnosis (3,5,8) and longer disease duration (3,5,8,13,29) have been repeatedly documented to correlate with manifestations of atherosclerosis in SLE. The present study extends the documentation of these characteristics as independent correlates of atherosclerosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the importance of inflammation in the genesis and progression of atherosclerosis (11,12), investigators have sought to determine whether specific aspects of SLE, a chronic inflammatory disease, are closely tied to the occurrence of myocardial infarction or the presence of subclinical atherosclerosis. Features of SLE that have been associated with clinical manifestations of coronary artery disease include older age at diagnosis (3,8), longer duration of SLE (3,8,13), higher damage index score (13), longer duration of steroid therapy (1,3,8,14), and higher concentrations of oxidized low-density lipoprotein (LDL) cholesterol and homocysteine (14). Features of SLE associated with the presence of subclinical atherosclerosis include older age at diagnosis (5), longer duration of SLE (5), longer duration of steroid therapy (4), less aggressive immunosuppressive therapy (5), and a higher damage index score (5).…”
mentioning
confidence: 99%
“…Several studies so far have confirmed the increased prevalence of arterial HT in these patients, ranging from 33% to 56% (de Leeuw, Freire et al 2006;Bellomio, Spindler et al 2009;Duarte, Couto et al 2009;Boucelma, Haddoum et al 2011;Sabio, Vargas-Hitos et al 2011). In an effort to investigate the contributors of HT in a cohort of 112 lupus patients, Sabio et al, reported that renal disease, insulin levels and disease activity indices such as Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) were independent predictors of HT in these subjects.…”
Section: Slementioning
confidence: 75%